Desenvolvimento de competências para a promoção da saúde na formação do enfermeiro - Luciana de Lourdes Queiroga Gontijo Netto Maia (2016)
The research takes as object skills for health promotion in nursing education. Considering the domains presented in consensus and international standards such as the Consensus of Galway and CompHP, studies have shown that the training of health professionals in general, does not prepare them to work in health promotion, due to the focus still predominantly biologicist, dressing and inarticulate of health practices. Investment in innovative curricula, with teaching-service and use of active learning methodologies can respond to this reality. The study aims to analyze the development of skills for health promotion in an undergraduate degree in Nursing. It is a qualitative research anchored in the theoretical and methodological framework of dialectics. Data were obtained from document analysis, interviews with graduates and focus groups with teachers of a higher education institution of Minas Gerais, Brazil. For supporting the analysis of qualitative data used the webQDA software. Data were submitted to Discourse Analysis Critical in Fairclough perspective. The results are discussed in three dimensions: The context of a course: continuities and ruptures to a new care model and teaching; Health Promotion and their skills: concept and practice in construction and Curricular strategies for the development of skills for health promotion. The findings indicate that the ongoing analysis bet a curricular organization in which comprehensiveness is highlighted as a goal of training without specificity for health promotion. The results show that skills for health promotion defined in specific consensus on the subject have been worked over the nurse training process. The focus of skills development focuses on implementation and experience allowing the student to the exercise of reflective practice on contexts and situations experienced the practical activities represented the main strategy for the development of skills for health promotion. The Teaching-Service-Community Integration Practice is seen as the moment of course that emphasizes the theory-practice articulation, early integration services into social reality, the teaching-service-community integration, teacher-student interaction and teamwork, constituting space for development expanded skills. The results indicate the need to overcome the insertion by the student's immersion in the context of professional practices to produce context, focus and purpose to the exercise of reflexivity. In addition, teacher training and systematization of different strategies considered in the curriculum are challenges identified in the study. It is concluded that the promotion of health as a movement against hegemonic, not yet occupied a prominent place in nursing education. To change this reality can be achieved with bets on reflexivity as a guiding principle of nursing education and the direction of education for the full development of skills for health promotion, building a new social practice.